2022
DOI: 10.1021/acs.jpcc.2c00102
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Free Alloyed Double Perovskites: An Emerging Class of Materials for Optoelectronic Applications

Abstract: Lead-free all-inorganic alloyed double perovskites have redefined the photovoltaic research in the recent past. However, a detailed study of their optical, excitonic, polaronic, and transport properties remains unexplored. Here, we investigate the variation of carrier-lattice interaction and optoelectronic properties of pristine as well as alloyed Cs2AgInCl6 double perovskites using a combined state-of-the-art many-body perturbation theory and density functional perturbation theory. Our results reveal that, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…Theoretically, the value of μ for Cs 2 AgInCl 6 was estimated to be 0.23 m 0 . 97 Our obtained value of μ for undoped Cs 2 AgInCl 6 is consistent with previously reported theoretical work. In this way, by analysing the closed-aperture Z -scan with the help of a two-band model we are able to estimate the value of μ , which is the fundamental physical parameter in perovskite materials.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Theoretically, the value of μ for Cs 2 AgInCl 6 was estimated to be 0.23 m 0 . 97 Our obtained value of μ for undoped Cs 2 AgInCl 6 is consistent with previously reported theoretical work. In this way, by analysing the closed-aperture Z -scan with the help of a two-band model we are able to estimate the value of μ , which is the fundamental physical parameter in perovskite materials.…”
Section: Resultssupporting
confidence: 92%
“…E B is the difference between the energy of an exciton (electrons and holes are bounded by a screened Coulomb interaction) and the energy of an unbound non-interacting electron–hole pair. If we took ε eff = 3.77 from the previous theoretical report, 97 we estimated E B = 0.23 eV. Therefore, from these analyses, it is possible to estimate the exciton binding energy also.…”
Section: Resultsmentioning
confidence: 99%
“…We can envisage the double perovskite as isolated metal halide octahedral anions surrounded by inorganic cations. A high exciton binding energy, more significant bandgaps, smaller band dispersions, and a higher charge carrier effective mass are the consequences of isolating metal halide octahedral anions. , The Cs 2 SnI 6– x Br x ( x = 0–3) structure has been widely investigated in Sn-based vacancy-ordered halide double perovskites …”
Section: Basic Properties Of Sn and Sn–pb Mixed Hybrid Perovskitesmentioning
confidence: 99%
“…A high exciton binding energy, more significant bandgaps, smaller band dispersions, and a higher charge carrier effective mass are the consequences of isolating metal halide octahedral anions. 63,64 The Cs 2 SnI 6−x Br x (x = 0−3) structure has been widely investigated in Sn-based vacancy-ordered halide double perovskites. 65 Other types of crystal structures were also observed.…”
Section: Basic Properties Of Sn and Sn−pb Mixed Hybrid Perovskitesmentioning
confidence: 99%
“…First-principles many-body perturbation theory within the GW approximation and the Bethe–Salpeter equation , (BSE) approach has played a particularly important role in quantitatively predicting the electronic and excited-state structure of halide perovskites. In particular, comparison of GW +BSE calculations with the Wannier–Mott model has demonstrated the hydrogenic nature of excitons in Pb-based halide perovskites , and in the double perovskite Cs 2 AgInCl 6 . , In contrast, we and others recently showed that the double perovskite family Cs 2 AgBX 6 (B = Bi or Sb, and X = Br or Cl) ,, exhibits resonant excitons with binding energies between 170 and 450 meV, which are strongly localized, with fine structural features that differ from those computed using the hydrogenic model. , We assigned the nonhydrogenic character of excitons in these halide double perovskites to their chemical heterogeneity giving rise to an anisotropic electronic structure and dielectric screening . For other halide double perovskites, optoelectronic properties and exciton binding energies were also shown to vary significantly. The picture that emerges from these reports suggests a rich landscape of excitons in halide double perovskites and calls for systematic mapping of this landscape using first-principles calculations.…”
mentioning
confidence: 99%